Breathing resistance in heat and moisture exchanging devices - Ainegren, M.; Hanstock, H.; Stenfors, N. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
The purpose of this study was to investigate the resistance to breathing (RES) in heat and moisture exchanging devices (HME) intended for use during physical activity in the cold. RES was investigated for seventeen HMEs, including different types of filters. In addition, the influence of headwind on RES was tested using four representative HMEs. HMEs were mounted to the face of an artificial head manufactured from ABS plastic. The HMEs were connected to a mechanical lung simulator, which delivered standardised inspiratory and expiratory air flow rates (V·, L/s). The delta pressure (?p, Pa) between ambient air and the air inside the HME was measured, whereupon RES was calculated. The results showed significant (p < 0.05) differences in RES between HMEs from different manufacturers, while the difference was smaller, and in some cases not significant (p > 0.05), between different models/filters within the same brand. The results also showed that RES was highly influenced by different ventilations and headwind conditions. RES increased with increased V· and, when a headwind was introduced, RES decreased during inspiration and increased during expiration. Calculations showed that the oxygen and energy cost for breathing through an HME was very small for most of the tested models. The effect of HME dead space on pulmonary gas fractions depends on the tidal volume. At large tidal volumes and ventilations, the effect of HMEs on pulmonary gas fractions becomes relatively small.